HUBUNGAN UTANG LUAR NEGERI DAN PERTUMBUHAN EKONOMI DI INDONESIA DENGAN PENDEKATAN GRANGER CAUSALITY - Chafrawi Akbar; Suriani Suriani; Ferayanti Ferayanti (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
Abstract Sustainable economic growth is a state goal for the achievement of prosperity and prosperity. Foreign debt has become one of the capital resources for the creation of economic development to promote good economic growth. However, foreign debt can backfire on a country if the country is unable to regulate and maintain foreign debt conditions. This study aims to see the causal relationship between foreign debt and economic growth in Indonesia with the time series data analysis method using the Granger Causality test. The variables used are foreign debt and economic growth. The results showed that economic growth has a one-way causal relationship to foreign debt, with an increase in economic growth. It is hoped that the government can reduce foreign debt.Keywords: Economic growth, foreign debt, Granger causality